Development of a Five-Tier Diagnostic Test to Reveal the Student Concept in Fluids - Setiawan, Doni; Eko Nugroho, Sunyoto; Made Darma Putra, Ngurah (Physics Communication, 2020)
This study aims to develop a five-tier form of fluid misconception diagnostic assessment and to reveal the profile of student’s conceptual understanding in maritime-based schools in the city of Tegal. This study used a 4D model (defining, designing, developing, and disseminating). The sampling technique used purposive sampling. The research samples were Bahari Vocational School Tegal, Al Maarif Vocational School Tegal, and Nahdlatul Ulama Senior High School Tegal. Methods of data collection used documentation, questionnaires, tests, and interviews. Expert validation states that the instrument was valid, has good readability, was easy to understand, and the sentence structure was correct. The reliability of the instrument is 0.958 and declared reliable. A total of 39 questions were categorized as medium, and one question was easy. The discrimination power of the questions obtained was that 30 questions were accepted, eight questions were received with a little improvement, and one question needed improvement. Seventy student misconceptions were identified from seven fluid sub-concepts. The biggest misconception, as much as 46.5% was found in the buoyancy sub-concept, while the smallest misconception was found in the application of Pascal's law at 35.2%. The most dominant misconception is that the deeper a point in the fluid is, the greater the buoyancy. Students assume that the greater the depth, the greater the fluid pressure, so that the buoyancy force is greater. Students believe that buoyancy is influenced by fluid pressure. This misconception is influenced by conceptual appreciation and intuition in daily life.